2003
DOI: 10.1080/0042098032000083812
|View full text |Cite
|
Sign up to set email alerts
|

Local Politics and the Demand for Public Education

Abstract: This paper expands on the school finance literature by using a political fragmentation index to calculate how political power affects educational spending in Virginia, USA. The methodology allows the comparison of different political voices relative to each other and the consideration of the role of the distribution of political power. Political fragmentation is considered across several different dimensions, including race, age, income and political parties. Using a demand for local public goods model, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There is similar, more limited, evidence of similar expenditure patterns from the USA. Two separate studies on transport infrastructure (Boschken 1998) and education (Colburn and Horowitz 2003) demonstrate, on a state level, that areas with a higher concentration of high socio‐economic status individuals spend more on high‐technology transport infrastructure (light rail as opposed to buses) and education. In the latter case the relationship is slightly parabolic, as those areas dominated by people on very high incomes (over $75,000 per annum) have a reduced expenditure as people exit to the private schooling system.…”
Section: Causal Theories and Evidencementioning
confidence: 99%
“…There is similar, more limited, evidence of similar expenditure patterns from the USA. Two separate studies on transport infrastructure (Boschken 1998) and education (Colburn and Horowitz 2003) demonstrate, on a state level, that areas with a higher concentration of high socio‐economic status individuals spend more on high‐technology transport infrastructure (light rail as opposed to buses) and education. In the latter case the relationship is slightly parabolic, as those areas dominated by people on very high incomes (over $75,000 per annum) have a reduced expenditure as people exit to the private schooling system.…”
Section: Causal Theories and Evidencementioning
confidence: 99%
“…This increase is what drives the sharp rise in the mismatch fragmentation index. Colburn and Horowitz (2003) used the fragmentation index to represent racial heterogeneity, though the authors only divided race into white and black. Using a cross-section of Virginia cities and counties, the authors found that the racial heterogeneity has a negative effect on education spending.…”
Section: Fragmentation Indexmentioning
confidence: 99%
“…In addition, expenditures per capita are found to depend on the per capita income (e.g., Fernandez and Rogerson, 1996). Colburn and Horowitz (2003) For German counties, Schwarz and Weishaupt (2013) provide an analysis on the determinants of per student expenditures for primary schools. The variation between Länder can mostly be explained by differences concerning the school system and all-day care.…”
Section: ) Local Expenditures For Primary and Secondary Educationmentioning
confidence: 99%